The homeodomain transcription factor TaHDZipI‐2 from wheat regulates frost tolerance, flowering time and spike development in transgenic barley. Issue 2 (15th March 2016) - Kovalchuk, Nataliya; Chew, William; Sornaraj, Pradeep; Borisjuk, Nikolai; Yang, Nannan; Singh, Rohan; Bazanova, Natalia; Shavrukov, Yuri; Guendel, Andre; Munz, Eberhard; Borisjuk, Ljudmilla; Langridge, Peter; et al.
Summary: Homeodomain leucine zipper class I (HD‐Zip I) transcription factors (TFs) play key roles in the regulation of plant growth and development under stresses. Functions of the TaHDZipI‐2 gene isolated from the endosperm of developing wheat grain were revealed. Molecular characterization of TaHDZipI‐2 protein included studies of its dimerisation, protein–DNA interactions and gene activation properties using pull‐down assays, in‐yeast methods and transient expression assays in wheat cells. The analysis of TaHDZipI‐2 gene functions was performed using transgenic barley plants. It included comparison of developmental phenotypes, yield components, grain quality, frost tolerance and the levels of expression of potential target genes in transgenic and control plants. Transgenic TaHDZipI‐2 lines showed characteristic phenotypic features that included reduced growth rates, reduced biomass, early flowering, light‐coloured leaves and narrowly elongated spikes. Transgenic lines produced 25–40% more seeds per spike than control plants, but with 50–60% smaller grain size. In vivo lipid imaging exposed changes in the distribution of lipids between the embryo and endosperm in transgenic seeds. Transgenic lines were significantly more tolerant to frost than control plants. Our data suggest the role of TaHDZipI‐2 in controlling several key processes underlying frost tolerance, transition to flowering and spike development.